Pengaruh Persepsi Kemudahan dan Inovasi Teknologi Terhadap Sikap dan Penggunaan Layanan QRIS: Studi Pada Wisatan Masjid Ceng Ho Pandaan Pasuruan - Mochamad Taufiq Hidayat; Antin Rakhmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
QRIS (Quick Response Code Indonesian Standard) has brought about a transformation in digital transactions, including donation practices at places of worship. This study examines the factors influencing the adoption and use of QRIS at the Cheng Ho Pandaan Mosque, focusing on perceived ease of use (X1), technological innovation (X2), and the role of attitude (Z) as a mediator of QRIS use (Y). The results show that perceived ease of use and technological innovation significantly and positively shape congregational attitudes. The more QRIS is perceived as easy and innovative, the more positive the congregational attitudes, which results in increased acceptance and use of the service. Furthermore, these two factors not only influence attitudes but also directly drive QRIS usage behavior; congregations are more likely to utilize it if the process is perceived as practical and offers innovative features. Positive attitudes prove to be a crucial link that translates perceptions of ease and innovation into concrete actions in donating through QRIS. These findings provide practical implications for the Cheng Ho Pandaan Mosque, namely the need to optimize transaction convenience and convey clear information about the benefits of QRIS. By creating a safe and convenient transaction experience supported by ongoing education, mosques can foster positive attitudes among their congregations, ultimately encouraging increased use of QRIS as a modern and efficient donation tool.